CLARIFICATION OF SASA GOURMET POWDER ADVERTISEMENT TOWARDS INDONESIAN PERCEPTIONS: A DISCOURSE ANALYSIS - Helmie, Jauhar; Al Khoeri, Arsyi Fadilah; Nugraha, Euis Nursifa Laila; Ramadhiani, Tassya Salsabila (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
This research describes the advertisement of Sasa Gourmet Powder which clarify issues that develop in Indonesian society about the use of MSG that is harmful for health. The source data used in this research is a “Sasa Gourmet Powder Advertisement #NikmatiHidupSepenuhnya (2021)” which has 29 seconds in long. The advertisement selected is available on Youtube. The aims of this research to reveal the purpose about why this advertisement is made and the social conditions underlying the making of the advertisement. This research applies descriptive qualitative method, which describes and explains the social world phenomenon or events. One of types in qualitative research is text analysis. This research utilizes text analysis in Sasa Gourmet Powder using Discourse analysis approach. The theory that used in this research is about Three-Dimensional Approach by Fairclough (1995). This theory explain about the relationship exists between social structures and discourse, because discourse influences social conventions, while social structures influence discourse. It focuses on analysis of language text, discourse practice (texts production and interpretations of text), and sociocultural practice. This research found that Sasa Gourmet Powder advertisements are designed to bring a new packaging from the company and to clarify its problems about MSG that have spread in society. With this advertisement, Sasa wants to show the fact that the MSG product does not cause stupidity. Sasa explained that its MSG products are safe to consume provided the limits of use are appropriate. Its products were also safely and halalled certified.Keywords: Discourse analysis, Advertising discourse, Fairclough’s Three-Dimensional theory, Sasa Gourmet Powder.